Response of integrated nutrient management (INM) on growth and yield attributes in tomato (Solanum lycopersicum L.) - D. P. Singh; Brijesh Kumar Maurya; Meenakshi Kumari; R. P. Singh; D. B. Singh; Prabhat Kumar (Annals of Agricultural Research, 2023)
An experiment was conducted to find out the suitable organic, inorganic and biofertilizer for integrated nutrient management in tomato at the Vegetable Research Station, Chandra Shekhar Azad University of Agriculture and Technology, Kanpur, Uttar Pradesh. This comprised of total eighteen treatments combinations of organic and inorganic nutrients including biofertilizer. The experiment was laid out in randomized completely block design (RBD) with three replications. The application of NPK (120:60:80 kg/ha) + FYM 10t/ ha + S @ 25 kg/ha + Azotobactor + Mixture of all micronutrients (T18) recorded significantly growth and has best performance over plant height (124.36 cm), leaf length (20.07), days to first fruiting (45.67), number of fruits per cluster (11.05) and fruit yield (308.73 q/ha) while T17 (NPK (120:60:80 kg/ha) + FYM 10t/ha + S@ 25kg/ha + Azotobactor) better performed in number of flowers/plant (51.26 flowers), Treatment T9 [NPK (120:60:80 kg/ha) + Mixture of all micronutrient (MM)] showed minimum days to flowering (39.46 days).